Consumer Behavior in the TikTok Era: An Islamic Consumption Perspective—A Systematic Literature Review - Mutia Rahmi; Malahayatie Malahayatie; Taufiq Taufiq (Al Dzahab, 2026)
Purpose: This study aims to examine the challenges and implementation of Islamic consumption principles in the digital era, particularly in shaping consumer behavior on TikTok. The study highlights key issues such as digital consumerism, algorithm-driven influence, and the emergence of hedonistic consumption patterns that may contradict Islamic values. Design/Methodology/Approach: This study employs a qualitative approach using a systematic literature review method. It synthesizes and critically evaluates prior studies on Islamic consumption and digital consumer behavior to develop a comprehensive understanding of consumption practices in the TikTok era. Findings: The findings reveal that the implementation of Islamic consumption principles on TikTok faces substantial challenges. The dominance of consumerist culture, limited literacy regarding halal and ethical consumption, and the persuasive nature of TikTok’s algorithm encourage impulsive and excessive consumption. These conditions create a gap between actual consumer behavior and Islamic values such as moderation (wasatiyyah) and responsibility. Research Implications: This study underscores the importance of strengthening Islamic consumer literacy and promoting ethical digital consumption. Strategic efforts such as value-based content creation, public education on halal consumption, and support for responsible consumer behavior are essential to align digital consumption practices with Islamic principles. This study also contributes theoretically by integrating Islamic consumption ethics with contemporary digital consumer behavior.